Analisis Kepemimpinan Transformasional, Motivasi Dan Kepuasan Kerja Serta Dampaknya Pada Kinerja Aparatur Sipil Negara Pada Kecamatan Sukorejo Kota Blitar - Agus Rianto (Universitas Islam Kadiri, 2020)
The purpose of this study was to determine the effect of transformational leadership, motivation and job satisfaction both simultaneously and partially on the performance of the State Civil Apparatus in Sukorejo District, Blitar City. Types of expanatiry research, technical analysis of multiple linear regression data. The results of the study show that there is no positive influence and significant Transformational Leadership on the Performance of State Civil Apparatus in Sukorejo District, Blitar City. There is a positive and significant influence on the motivation of the State Civil Apparatus in Sukorejo District, Blitar City. There is a positive and significant influence of Job Satisfaction on the State Civil Apparatus in Sukorejo District, Blitar City. There is a positive and significant influence of Transformational Leadership, Motivation and Job Satisfaction simultaneously on the Performance of the State Civil Apparatus in Sukorejo District, Blitar City